Correlating MRI-based brain volumetry and cognitive assessment in down syndrome patients - Hamadelseed, Osama; Skutella, Thomas (Research Square, 2022)
INTRODUCTION: Down syndrome (DS) is the most common genetic cause of intellectual disability. Here, we use magnetic resonance imaging (MRI) on children and adults with DS to characterize changes in the volume of specific brain structures involved in memory and language and their relationship to features of cognitive-behavioral phenotypes.METHODS: Thirteen children and adults with the DS phenotype and 12 age- and gender-matched healthy controls were analyzed by MRI and underwent a psychological evaluation for language and cognitive abilities.RESULTS: The neuropsychological profile of DS patients showed deficits in different cognition and language domains in correlation with reduced volumes of specific regional and subregional brain structures.CONCLUSIONS: The memory functions and language skills affected in our DS patients correlate significantly with the reduced volume of specific brain regions, allowing us to understand DS's cognitive-behavioral phenotype. Our results provide an essential basis for early intervention and the design of rehabilitation management protocols.
Gesehen am 31.01.2022